Corporate Secretary Professional Expertise and Annual Report Readability - Monicha Octaviani; Iman Harymawan (JASF: Journal of Accounting and Strategic Finance, 2022)
This paper aims to examines the relationship between professional corporate secretary expertise and annual report readability of 1,476 observations from all companies listed in the Indonesia Stock Exchange from 2014-2018 using OLS Regression with STATA 15.0. The findings obtained from this research are the legal expertise possessed by the corporate secretary will make the company's financial statements easier to understand. Meanwhile, the accounting expertise of the corporate secretary has no significant effect on the annual report readability. However, the annual report readability of firms with a corporate secretary with international expertise will be more readable. For company management, the results of this study have implications for consideration to involve professional expertise, such as legal expertise and international experience, as a part of qualifications in appointing corporate secretaries to improve the quality of information disclosure. Furthermore, this paper increases the understanding of the corporate secretary’s characteristics and its effect on the company’s annual report readability as a tool to measure the quality of information disclosure to reduce problems related to asymmetric information.